Convective transport of pulsatile multilayer hybrid nanofluid flow in a composite porous channel - Shaik Jakeer; Seethi Reddy Reddisekhar Reddy; Maduru Lakshmi Rupa; Hayath Thameem Basha (Nonlinear Analysis)
Multilayer fluid models play a crucial role in comprehending fluid–fluid and fluid–nanoparticle interactions within the petroleum industry, geophysics, and plasma physics due to their diverse industrial applications. The current research aims to investigate the impact of a heat source/sink on a non-Newtonian hybrid nanofluid that saturates a porous medium positioned between a transparent viscous fluid filling a vertical channel. The model governing nonlinear coupled differential equations are nondimensionalized using appropriate fundamental quantities. Subsequently, the regular perturbation method is employed to solve the transformed dimensionless governing equations. Upon comparing the data, it is evident that current results closely align with the previously published findings. The parameter Q2 causes an increase in both θs(ζ) and θt(ζ) across all three regions. Increasing Casson parameter leads to a decrease in θt(ζ).